Extension Communication Fisherwomen in Ecotourism Management in Small Islands - Khodijah Ismail; Sayyidah Nur Habibah (Lasigo Akademia Indonesia, 2020)
The purpose of this study was to determine the effectiveness of extension communication among fisherwomen in the management of eco-tourism. This research was conducted in the tourist area of Benan Island, Lingga Regency, Riau Islands Province, using a mixed method, which is a combination of qualitative and quantitative research methods. The results of the analysis conclude that fisherwomen are said to be effective in conducting extension education to support sustainable eco-tourism management in the village. This is seen from the effectiveness value of several components in the effective category range (330-540), among others the frequency of Extension conducted by fisherwomen to the family environment and surrounding communities has a value of 380, the value of the level of knowledge about the goals of eco-tourism management obtained by the community from extension communication is 370, and the value of implementing sustainable eco-tourism management by the surrounding community of 360. Extension communication methods with individual direct dialogue are considered more effective (380) compared to direct group dialogue (253). This indicates that fisherwomen need a higher intensity of training in order to increase their knowledge and skills as well as their involvement in ecotourism management in the village.